Conceptual Study of Proactive Attitude in Micro, Small and Medium Enterprises (MSMEs) - Yandi, Andri; Winarno, Agung; Pratikto, Heri (Greenation International Journal of Tourism and Management, 2024)
This study is a conceptual review that examines the role of proactive entrepreneurial behavior in Micro, Small, and Medium Enterprises (MSMEs) in relation to exploratory innovation, digital marketing strategies, and business performance. The study is divided into several sections. First, the literature review focuses on proactive attitudes. Second, the research model and propositions developed in this study are based on a review of previous research, such as the relationship between proactiveness and exploratory innovation, proactiveness and digital marketing, as well as proactiveness and MSME performance. Proactive behavior in the entrepreneurial context involves initiative, adaptability, and the courage to seize opportunities, enabling MSMEs to survive and grow amidst increasingly intense competition. Exploratory innovation provides MSMEs with a competitive advantage by creating new products or services that meet the dynamic needs of the market. The adoption of digital marketing strategies enhances market reach and allows MSMEs to leverage technology to attract and retain customers. Overall, this study demonstrates that proactive entrepreneurial behavior not only drives innovation and digital marketing but also significantly impacts MSME performance positively. These findings highlight the importance of fostering proactive attitudes among MSME entrepreneurs to promote business sustainability through responsive and adaptive approaches to market changes.